Aspectos epidemiológicos, clínicos e anatomopatológicos de surtos de língua azul em ovinos na região central do Rio Grande do Sul - Bianchi, Ronaldo Michel (2016)
Bluetongue (BT) is an infectious disease caused by bluetongue virus (BTV), which is transmitted by biting midges of the genus Culicoides, and affects domestic and wild ruminants, but its clinical manifestation is seen basically in sheep. Currently, 26 BTV serotypes are recognized worldwide. However, information about the disease in Brazil are limited, as only two BTV serotypes have been reported. Serological surveys reveal that Rio Grande do Sul (RS) has the lowest prevalence rates of infection among Brazilian states. This article describes the clinical, pathological and epidemiological aspects of 17 outbreaks of BT disease in sheep in the Central Region of RS state, Southern Brazil. Affected farms were visited for clinical examination, necropsy, sample collection and epidemiological investigation. The outbreaks were seasonal and occurred during the summer and fall. Of the 884 sheep in 17 small herds, 180 (20.4%) were affected. All ages of Texel and mixed breed sheep were affected. However, lambs (younger than one year) had higher morbidity than adult sheep. The most frequent clinical signs were anorexia, lethargy, loss of body condition, facial swelling mainly involving the lips, and greenish seromucous nasal discharge. Pulmonary edema, cardiac, skeletal muscle and esophageal striated muscle necrosis were the most prevalent findings. Erosive and ulcerative lesions in the upper gastrointestinal tract, and hemorrhage in the pulmonary artery also were common. The bluetongue virus (BTV) genome was detected by RT-PCR in blood, spleen, and lungs samples of 21 animals from 17 outbreaks. The virus involved in the outbreak 3 was isolated and shown to belong to serotype 17, for the first time reported in Brazil. Serology performed by agar gel immunodiffusion test (AGID) in 20 contact cattle showed seroconversion to BTV in 17 animals. In summary, our data support the BTV as the etiological agent of the outbreaks and indicate that the central region of RS is an area at risk for BT in sheep, a disease previously not recognized in the region.